Avaliação custo benefício - ACB da politica pública de intervenção urbana - parque linear do rio Ressaca em São José dos Pinhais, Paraná - Guilherme, Marcelo (2024)
This study aims to propose a municipal bill for the evaluation of projects and programs, based on the cost-benefit analysis (CBA) of the public policy for the implementation of the Rio Ressaca Linear Park in São José dos Pinhais, Paraná, 17 years after its implementation. The methodology used is a case study, including documentary and bibliographic research, as well as the application of a questionnaire to municipal officials working in public policy evaluation. After requesting information from the Municipal Secretariats involved in the development and execution of the public policy, the absence of some data was identified. Additionally, the data obtained, after analysis, were found to be of insufficient quality for systematic organization and use in an ex post CBA. Given this scenario, a complementary questionnaire was applied to municipal officials to assess whether the lack or quality of the data is related to their perception of the importance of public policy evaluation and their knowledge of the CBA method. Although conducting the CBA was not possible, the data obtained were analyzed separately in comparison to the estimates from the ex ante CBA, revealing a discrepancy of more than 150% in investment costs. It was concluded that, due to challenges in obtaining and analyzing data, as well as the limited knowledge of municipal officials regarding CBA, a specific municipal law for public policy evaluation, based on Ordinance Sepec/ME-Ipea No. 188/2022, could contribute to generating high-quality data that would enable the execution of CBA. Based on the results obtained, this study proposes a complementary bill to amend the municipality9s Organic Law, aiming to improve data access and quality, allowing for the implementation of CBA in accordance with national evaluation standards.